Assessment Of Knowledge and Attitude of Antenatal Mothers Towards Breastfeeding - Nigam , Richa; Sinha , Umesh (National Journal of Community Medicine, 2012)
Introduction: Breastfeeding is an unequalled way of providing ideal food for the healthy growth and development of infants. Antenatal counseling is very useful for ensuring breastfeeding in postnatal period Objectives: Assessment of antenatal services with respect to information about benefits of breastfeeding practices and Assessment of knowledge about benefits of breastfeeding amongst the beneficiaries of the hospitals under study. Methodology: Antenatal mothers attending the OPD were interviewed about their knowledge regarding breastfeeding practices and about the hospital services for imparting this knowledge or information. Results: Out of total 200 antenatal beneficiaries 81.5%were having knowledge about benefits of exclusive breast feeding 37 (18.5%) answered don’t know (p value >0.05 not significant statistically). Out of total 200 antenatal beneficiaries 61 (30.5%) were informed about exclusive breast feeding and 139(69.5%) were not informed, (p value <0.05 significant statistically). Conclusion: Majority of ANC women attending the OPD were not aware about Exclusive Breast Feeding (EBF), however they were having good knowledge about the benefits of breast feeding. The major source of information being doctors rather than paramedical staff, calls for more attention and training of nurses and other supporting hospital staff regarding Baby Friendly Hospital.